2010
DOI: 10.1007/s00011-010-0167-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune depression in musculoskeletal trauma

Abstract: The immune responses after musculoskeletal trauma are physiological reactions of the organism to restore homeostasis. An imbalance between the early systemic inflammatory response syndrome and the later compensatory anti-inflammatory response syndrome may be responsible for organ dysfunction and increased susceptibility to infections. Cytokines are known to be integral components of the immune response, and the balance or imbalance of the different cytokines partly controls the clinical course in the patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 81 publications
3
42
0
2
Order By: Relevance
“…In patients with severe injuries this increase may persist longer [2,3]. In such patients the "secondary hit" inflammatory reaction, following ETC procedures, may aggravate the acute systemic inflammatory reaction syndrome (SIRS), and may lead to development of acute respiratory distress syndrome (ARDS) and multiple organ failure (MOF) with a relatively high morbidity and mortality [2,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with severe injuries this increase may persist longer [2,3]. In such patients the "secondary hit" inflammatory reaction, following ETC procedures, may aggravate the acute systemic inflammatory reaction syndrome (SIRS), and may lead to development of acute respiratory distress syndrome (ARDS) and multiple organ failure (MOF) with a relatively high morbidity and mortality [2,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies found that anesthetic agents had significant influence on serum cytokines in patients who underwent surgeries (Dermitzaki et al, 2009;Reikerås et al, 2010). Propofol, as one of the anesthetic agents commonly used in clinic, has favorable sedation, anti-inflammatory responses and anti-oxidation characteristics (Cavalca et al, 2008;Gonzalez-Correa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…They affect a wide www.intechopen.com variety of cells to induce fever, production of cytokines, endothelial gene regulation, chemotaxis, leukocyte adherence, and activation of fibroblasts. They are responsible for the systemic effects of inflammation, such as loss of appetite and tachycardia (Reikeras, 2010). IL-6 is another cytokine that appears to be critical in the inflammatory cascade in the setting of trauma.…”
Section: Inflammatory Mediatorsmentioning
confidence: 99%
“…IL-6 levels are elevated 60 minutes after trauma (or surgery) and decline over days 2 to 5 after trauma. Importantly, the magnitude of IL-6 elevation after mechanical trauma can be used as a reliable marker for the magnitude of systemic inflammation and correlates with the risk of post-injury complications (Reikeras, 2010;Biffl et al, 1996;. IL-6 appears to be responsible for regulating the acute phase response (Reikeras, 2010).…”
Section: Inflammatory Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation